2023
DOI: 10.2215/cjn.0000000000000330
|View full text |Cite
|
Sign up to set email alerts
|

Performance of ChatGPT on Nephrology Test Questions

Jing Miao,
Charat Thongprayoon,
Oscar A. Garcia Valencia
et al.

Abstract: Background: ChatGPT is a novel tool that allows people to engage in conversations with an advanced machine learning model. ChatGPT's performance in the United States Medical Licensing Examination is comparable to a successful candidate’s performance. However, its performance in nephrology field remains undetermined. This study assessed ChatGPT's capabilities in answering nephrology test questions. Methods: Questions sourced from Nephrology Self-Assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…This niche area calls for innovative tools and strategies. Emerging technologies like LLMs and chatbots [38][39][40][41][42][43] offer promising avenues to enhance patient care and are increasingly relevant for healthcare professionals in this field (Table 3).…”
Section: Long-term Aki Effects and Preventive Measuresmentioning
confidence: 99%
“…This niche area calls for innovative tools and strategies. Emerging technologies like LLMs and chatbots [38][39][40][41][42][43] offer promising avenues to enhance patient care and are increasingly relevant for healthcare professionals in this field (Table 3).…”
Section: Long-term Aki Effects and Preventive Measuresmentioning
confidence: 99%
“…18 , 19 , 20 , 21 , 22 Our findings show that GPT‐4′s accuracy in responding to questions related to hypertension has increased by 20%, achieving a 77% success rate. 10 Despite the need for a subscription to access GPT‐4, its enhanced performance strongly supports its recommended use.…”
Section: Approaches For Increasing Chatgpt's Performancementioning
confidence: 99%
“… 6 AI, particularly through ChatGPT, introduces a new dimension to clinical decision‐making. 7 Studies have demonstrated ChatGPT's efficacy in providing relevant advice for cardiovascular disease prevention and hypertension management, 8 , 9 , 10 indicating its potential to improve clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…11 ChatGPT-3.5 and ChatGPT-4 have garnered attention due to its ability to comprehend and respond to intricate queries, making it a prospective resource for individuals seeking drug-related information. 12 , 13 However, it is uncertain the extent to which these large language models can be used for guiding non-prescription medication and supplement safety considerations in patients with kidney disease. 14 We therefore sought to evaluate ChatGPT-3.5 and ChatGPT-4's performance in assessing the safety of over-the-counter medications and supplements in patients with kidney disease, while simultaneously comparing its performance to that of Micromedex.…”
Section: Introductionmentioning
confidence: 99%